Radioimaging Evaluation of Primary Bone Tumors and Tumor like Lesions - Sunil K Vatukiya; Bhautik Kapadia (Asian Journal of Medical Radiological Research, 2020)
Background: Bone tumour is relatively rarely encountered by radiologist, so sometimes it creates diagnostic difficulty. Aim over study was   to determine the X-ray CT and MRI characteristics of different primary bone tumours and tumour like lesion and correlation of radiologic diagnosis with histopathologic diagnosis whenever possible. To understand the advantages and limitations of different radio-imaging techniques. Subjects and Methods: We have studied total 45 cases of primary bone tumour and tumour like lesions during study of 15 months duration in department of Radiodiagnosis, Baroda Medical College, Vadodara, Gujarat, India. First radiological diagnosis and differential diagnosis was given than histopathologic examination was done in all malignant and indeterminate lesions for final diagnosis. Results:  Out of 45 patients   21 (46.6%) were female and 24 (53.3%) were male. Benign and malignant lesions were 69% and 31% respectively. Multiple lesions were common with osteochondroma, hemangioma and multiple myeloma. Most common malignant tumour was osteosarcoma and benign tumour was osteochondroma. Pathologic fracture was seen in 6 patients but out of them 2 fractures were missed on radiograph. Skip lesions were seen in two malignant lesions which was missed on radiograph and CT but it was easily detected on MRI. Conclusion: Radiography is baseline investigation for evaluation of bone tumor and tumour like lesions. Pathological fracture and matrix mineralization can be better seen on CT. MR is superior in detection skip lesion, soft tissue and marrow extension.